Associations of urinary phthalate metabolites with risk of papillary thyroid cancer. (February 2020) - Miao, Hongjian; Liu, Xin; Li, Jingguang; Zhang, Lei; Zhao, Yunfeng; Liu, Shaoyan; Ni, Song; Wu, Yongning
Abstract: Some studies have revealed thyrotoxicity of phthalates; however, associations of phthalate exposure with papillary thyroid cancer (PTC) remain unclear. We conducted a pair-matching case-control study of 111 PTC cases and 111 age- and sex-matched non-PTC controls to examine associations between urinary concentrations of phthalate metabolites and PTC. Phthalate metabolites were determined in fasting urine specimens by ultra-performance liquid chromatography – tandem mass spectrometry (UPLC-MS/MS). After adjusting for potential confounders and other phthalate metabolites, the concentrations of the sum of di (2-ethylhexly) phthalate (DEHP) metabolites in urine were positively associated with PTC [odds ratio (OR) = 5.35; 95% confidence interval (CI): 1.61–17.83], suggesting the effect of phthalates exposure on PTC development. The findings require confirmation. Graphical abstract: Image 1 Highlights: Associations of urinary phthalate metabolites with PTC risk were examined. DEHP metabolites were positively associated with increased risk of PTC. The associations were influenced by urinary iodine levels.